Additive manufacturing of Trabecular Titanium orthopedic implants. (12th February 2015) - Regis, M.; Marin, E.; Fedrizzi, L.; Pressacco, M.
Abstract: Abstract : The long-term success of an orthopedic implant largely depends on the extent of its osseointegration in the surrounding bone. During recent decades, there have been several attempts to develop porous structures and coatings in order to maximize the bone ingrowth on prosthesis surfaces. Innovative additive manufacturing technologies, such as electron beam melting (EBM), which are based upon building components by adding layers of material rather than by removing material from a raw shape, can provide a breakthrough solution, both to overcome the major limitations of the actual technologies and to significantly enhance the performance of porous scaffolds. This article reviews the latest developments in EBM technology applied to the preparation of highly biocompatible porous materials such as Trabecular Titanium and the production of orthopedic prostheses with enhanced characteristics.